Age Distribution, Saving and Consumption in Sweden - Lennart Berg (Uppsala University, Department of Economics, 1996)
This paper focuses on an empirical analysis of the dependency between age structure and aggregate consumption and the composition of aggregate savings. In a long-run consumption function of life cycle type, different demographic variables have a conclusive, statistically significant effect. In investigating the link between demographic variables and the composition of aggregate savings, a simple simultaneous model is used, and a saving function and a house price equation are estimated. The result even here is that age composition matters for house price and savings. This conclusion is also made visible by a simulation experiment. Finally is the model used to ascertain the effect on the recent Swedish tax reform on savings.
urn:nbn:se:uu:diva-2371
Keywords: 330